Ruthenium complexes with vinyl, styryl, and vinylpyrenyl ligands: a case of non-innocence in organometallic chemistry - Maurer, Jörg; Linseis, Michael; Sarkar, Biprajit; Schwederski, Brigitte; Niemeyer, Mark; Kaim, Wolfgang; Zalis, Stanislav; Anson, Chris; Zabel, Manfred; Winter, Rainer F (Journal of the American Chemical Society, 2008)
We herein describe a systematic account of mononuclear ruthenium vinyl complexes L-Ru-CH=CH-R where the phosphine ligands at the (PR'3)2Ru(CO)Cl=Ru moiety, the coordination number at the metal (L = 4-ethylisonicotinate or a vacant coordination site) and the substituent R (R = nbutyl, phenyl, 1-pyrenyl) have been varied. Structures of the enynyl complex Ru(CO)Cl(PPh3)2(eta1:eta2-nBuHC=CHCCnBu), which results from the coupling of the hexenyl ligand of complex 1a with another molecule of 1-hexyne, of the hexenyl complexes (nBuCH=CH)Ru(CO)Cl(PiPr3)2 (1c) and (nBuCH=CH)Ru(CO)Cl(PPh3)2(NC5H4COOEt-4) (1b), and of the pyrenyl complexes (1-Pyr-CH=CH)Ru(CO)Cl(PiPr3)2 (3c) and (1-Pyr-CH=CH)Ru(CO)Cl(PPh3)3 (3a-P) have been established by X-ray crystallography. All vinyl complexes undergo a one-electron oxidation at fairly low potentials and a second oxidation at more positive potentials. Anodic half-wave or peak potentials show a progressive shift to lower values as pi-conjugation within the vinyl ligand increases. Carbonyl band shifts of the metal-bonded CO ligand upon monooxidation are significantly smaller than is expected of a metal-centered oxidation process and are further diminished as the vinyl CH=CH entity is incorporated into a more extended pi-system. ESR spectra of the electrogenerated radical cations display negligible g-value anisotropies and small deviations of the average g-value from that of the free electron. The vinyl ligands thus strongly contribute to or even dominate the anodic oxidation processes. This renders them a class of truly "non-innocent" ligands in organometallic ruthenium chemistry. Experimental findings are fully supported by quantum chemical calculations: The contribution of the vinyl ligand to the HOMO increases from 46% (Ru-vinyl delocalized) to 84% (vinyl dominated) as R changes from nbutyl to 1-pyrenyl.